2019
DOI: 10.29333/iji.2019.1242a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Writing Performance of Iranian IELTS Candidates Facing Chart Topics vs. Table Topics in Academic Writing (Task1)

Abstract: The present study aimed at investigating whether academic IELTS candidates perform differently in writing on either a chart topic or a table topic of the IELTS writing task 1 with regard to the four IELTS writing marking criteria i.e. task achievement, coherence and cohesion, lexical resource, and grammar range and accuracy. The study adopted a mixed methods approach. To this end, 45 candidates participated in the study. In the beginning, the participants were asked to write on a chart topic of the IELTS writi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The next activity which the IELTS trainers do is making use of their experiences. This activity is categorized as independent learning (Ahmadi et al, 2019;Jones & Dexter, 2014). More particularly, the trainers utilized their experiences both in their pre-service education when they learned IELTS and in their in-service IELTS teaching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next activity which the IELTS trainers do is making use of their experiences. This activity is categorized as independent learning (Ahmadi et al, 2019;Jones & Dexter, 2014). More particularly, the trainers utilized their experiences both in their pre-service education when they learned IELTS and in their in-service IELTS teaching.…”
Section: Resultsmentioning
confidence: 99%
“…By combining pre-service and in-service experiences, the trainers can give appropriate teaching applications for their IELTS learners since they get insights into both students' and teachers' sides. This point is relevant with Ahmadi et al (2019) statement that reflecting self-experiences is a part of understanding others that is relevant to the teacher's role who applied interpersonal relationship in their teaching practice. All research subjects agreed that their experiences are essential points in their IELTS teaching career, which is varied for each of them, notably how they adjusted themselves in various class sizes.…”
Section: Resultsmentioning
confidence: 99%
“…To start with, most studies, as discussed in the literature, blame test-takers for scoring low in writing by highlighting their weaknesses. Test-takers are suggested to be either weak in different aspects of writing (see, for example, Ahmadi, et al, 2019;Maharani & Setyarini, 2019) or unfamiliar with IELTS genres of writing (Pearson, 2019). Unlike the studies mentioned in the literature review, this investigation has adopted a different perspective and provided a chance for the test-takers to voice their concerns.…”
Section: Discussionmentioning
confidence: 98%
“…They found that diagram analysis was more difficult for Iranian test-takers than the interpretation of bar charts. Ahmadi et al (2019) found that Iranian test-takers had more vocabulary problems with tables than with charts. O' Loughlin and Wigglesworth (2003) found that task difficulty was not consistent in Task 1, and that tasks that were simpler with less information led to test-takers in Australia achieving better performances.…”
Section: Literature Reviewmentioning
confidence: 95%
“…It means that if any Indonesian student plans to pursue their further studies abroad, they are required to take an IELTS exam with the targeted score. Ahmadi et al (2019) stated that IELTS is a task-based test assessing the four language skills of listening, reading, writing, and speaking, where the total duration of the test will take around 2 hours 45 minutes in one seat. As evidence of English language proficiency, IELTS academic is of pivotal importance for educational success in academic institutions.…”
Section: Grammar and Listeningmentioning
confidence: 99%